Effect of the application of stem cells for tendon injuries in sporting horses - Tuemmers, C; Rebolledo, N; Aguilera, R (Archivos de medicina veterinaria, 2012)
Finding a cure for tendonitis in sporting horses has been a challenge for veterinarians during a long time. Regenerative medicine using stem cells from the patient has emerged as an innovative method that allows breaking the barriers of finding a resolution that can be maintained over time. Additionally, the benefits surpass those of traditional therapies, which do not facilitate full recovery. Bone marrow and adipose tissue have been described as major sources for stem cell extraction. The use of both tissues involves different processes of cell harvesting and concentration, which eventually yield a product that must be injected into the affected region, or in the center of a typical core lesion. The expected result is the regeneration of the tendon without excess fibrous tissue, properly aligned tendon fibers and decreased inflammatory infiltration and hemorrhage. Following a rehabilitation program that includes resting and progressive exercise, the horse returns to its previous competitive condition. This therapy is feasible because the techniques for extraction from both sources are simple. If the two techniques are compared, adipose tissue extraction is easier because it requires fewer elements and less time. Both therapies, however, can be executed in the acute stage of injury. The use of stem cells in horses is the subject of a growing body research that has already yielded encouraging results.